2018
DOI: 10.1038/s41418-018-0058-y
|View full text |Cite
|
Sign up to set email alerts
|

RGMa mediates reactive astrogliosis and glial scar formation through TGFβ1/Smad2/3 signaling after stroke

Abstract: In response to stroke, astrocytes become reactive astrogliosis and are a major component of a glial scar. This results in the formation of both a physical and chemical (production of chondroitin sulfate proteoglycans) barrier, which prevent neurite regeneration that, in turn, interferes with functional recovery. However, the mechanisms of reactive astrogliosis and glial scar formation are poorly understood. In this work, we hypothesized that repulsive guidance molecule a (RGMa) regulate reactive astrogliosis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(78 citation statements)
references
References 54 publications
2
67
0
Order By: Relevance
“…Repulsive guidance molecule A (RGMa), a GPI-linked glycoprotein, inhibits axon growth by interacting with its neuronal receptor neogenin, but it also promotes reactive astrogliosis and glial scar formation by activating the TGFβ1-Smad2/3 signaling pathway and preventing neurological functional recovery after stroke (Zhang et al, 2018 ). Consistently, treatments with RGMa antibodies promoted axon regeneration and functional recovery in adult rodents with SCI and also showed a trend toward reducing CSPG expression around the lesion (Hata et al, 2006 ; Mothe et al, 2017 ).…”
Section: Numerous Intracellular Signals Convey Cspg Inhibition On Neumentioning
confidence: 99%
“…Repulsive guidance molecule A (RGMa), a GPI-linked glycoprotein, inhibits axon growth by interacting with its neuronal receptor neogenin, but it also promotes reactive astrogliosis and glial scar formation by activating the TGFβ1-Smad2/3 signaling pathway and preventing neurological functional recovery after stroke (Zhang et al, 2018 ). Consistently, treatments with RGMa antibodies promoted axon regeneration and functional recovery in adult rodents with SCI and also showed a trend toward reducing CSPG expression around the lesion (Hata et al, 2006 ; Mothe et al, 2017 ).…”
Section: Numerous Intracellular Signals Convey Cspg Inhibition On Neumentioning
confidence: 99%
“…Focal cerebral ischemia and reperfusion injury was induced by MCAO/R in mice using an intraluminal filament technique, as described previously 36 . In brief, adult male mice weighing 22.5-24 g were fasted for 12 h but were allowed free access to water before surgery.…”
Section: The Middle Cerebral Artery Occlusion/reperfusion Modelmentioning
confidence: 99%
“…For instance, both RGMa and DRAGON (RGMb) are expressed in the nervous system and enhance BMP signalling by binding with BMP ligands, BMP type I receptors, and BMP type II receptors . However, a more recent study demonstrated that RGMa also facilitated TGFβ1/Smad2/3 signalling by interacting with TGF‐β1 receptor activin‐like kinase 5 and Smad2/3 during glial scar formation, suggesting an additional role for RGM family members in TGF‐β1 signalling. Unlike RGMa and RGMb, hemojuvelin (also known as HJV or RGMc) is not detected in the brain but is highly expressed in skeletal muscle, heart, and liver .…”
Section: Introductionmentioning
confidence: 99%